Writing at work : how to write clearly, effectively and professionally - James, Neil, 1966- (Crows Nest, N.S.W. : Allen & Unwin, 2007)
Effective writing is a key to professional success.
Includes index.
Bibliography: p 330-342.
Shamim
Keywords: English language -- Written English; Report writing; Technical writing